SARS, Avian Flu, and Other Challenges for China’s Political, Social, and Economic Transformation - Dumbaugh, Kerry; Morrison, Wayne (Library of Congress. Congressional Research Service., 2004)
This document discusses the political, social, and economic impact of SARS, avian flu, and other health issues on China as well as policy implications for the U.S., Hong Kong, and Taiwan.